2020
DOI: 10.1055/s-0040-1719154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Modifiable Risk Factors on Long-Term Outcomes after Coronary Artery Bypass Surgery

Abstract: Background Risk factors control and secondary prevention measures are often reported to be suboptimal in patients undergoing coronary artery bypass grafting (CABG) and may lead to worse clinical outcomes. We aimed to examine potentially modifiable risk factors in patients undergoing CABG and investigate their association with long-term coronary events. Methods Cardiovascular risk factors were recorded preoperatively in the setting of a cardiac catheterization laboratory and were analyzed in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…A potential explanation may be the confounding effects of major predictors such as smoking. Smoking patients are known to have lower BMIs [ 38 , 39 ], while they carry a high risk of short- and long-term adverse cardiac events after CABG [ 40 , 41 ]. In this study, we performed comprehensive adjustments for many potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation may be the confounding effects of major predictors such as smoking. Smoking patients are known to have lower BMIs [ 38 , 39 ], while they carry a high risk of short- and long-term adverse cardiac events after CABG [ 40 , 41 ]. In this study, we performed comprehensive adjustments for many potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that within 5 years after CABG, 20%-30% patients experienced MACE and 15% died (22,23). Due to the high residual risk of cardiovascular morbidity and mortality, implantation and optimization of postoperative secondary prevention is highly recommended (24,25). Management of lipid abnormalities remains one of the primary goals in secondary prevention, for the reason that hyperlipidemia is associated with increased future cardiovascular events and graft deterioration (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Modifikasi terhadap faktor risiko harus ditargetkan pada modifikasi dini terhadap perubahan gaya hidup dan pemberian obat yang sesuai. Peran pencegahan sekunder mengukur dan mengontrol faktor risiko dalam rangka mengurangi kejadian kardiovaskuler yang tidak diharapkan dan terjadinya kematian termasuk kejadian setelah pembedahan (Leviner, Zafrir, Jaffe, Saliba, Flugelman, & Sharoni, 2021).…”
Section: Pembahasanunclassified